Enhancing Students’ Arabic Learning Outcomes Using Kinemaster-Based Audiovisual Media: A Case in Al-Irsyad Junior High School, Banyuwangi, East Java - Syarofah Syarofah; Murdiono Murdiono; Anisatu Thoyyibah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Persistent underachievement in Arabic language learning particularly within post-COVID-19 online learning environments remains a critical concern. This study explores the impact of Kinemaster-based audiovisual media on improving Arabic learning outcomes among seventh-grade students at Al-Irsyad Junior High School in Banyuwangi, East Java. Positioned within the growing discourse on technology-integrated pedagogy, the research evaluates how digital media tools influence student engagement and academic success. Employing a quantitative associative design with pretest-posttest methodology, data were gathered from 23 students through observations, tests, questionnaires, and documentation. Statistical analysis via SPSS, including normality tests, paired sample T-tests, and N-Gain calculations, indicated a significant performance increase from a total posttest score of 1424 to 1882 with a significance value of 0.001. The N-Gain score of 52.28 categorized the improvement as moderately effective. These results affirm the pedagogical potential of Kinemaster-based audiovisual media in Arabic instruction, offering promising implications for fostering student-centered, multimedia-enhanced learning. Further investigations are recommended to assess scalability and the mediating role of individual learner characteristics.